Water quality monitoring system on board USV - Tanesh, Maran (2021)
Nowadays, water pollution is the worldwide major problem with each country still cannot maintain their water cleanness for daily use. This project is to develop and design a water quality sampling detector that has the same functionality as the previous product but has a much lower cost budget and can easily set up in the specific area as the project is compact and portable. This project consists of two main circuits that are combined to produce a great output as it can save the lives of people. The first circuit is about the control circuit which two main components are the brush-less motor and servo motor that both of which are connected to one Arduino board. The second circuit is about the sensor circuit which three common sensors that require to determine the quality level of water and all of them being connected to the same Arduino board. Besides, these two main circuits will be placed on a boat that has been designed suitable to move in a river or drainage. This project is very useful to monitor the water quality as it can be mobilized alongside the river or drainage to read different data from the very beginning of the river until the end of the estuary. Unmanned Surface Vehicle (USV) as the name goes is a transportation method that transports things or objects to the intended location. It does not need human intervention for its operation. The use of USV nowadays has become important as the potential of dangers faced by the human to operate the vehicle becoming more dangerous. Hence, it might endanger the life of the operator. For the vehicle to operate without human it needs to be controlled wireless. This project explored the use of IoT such as wireless communication, web server, cloud database, and mobile application. Wi-Fi is used as the communication medium to control the USV via mobile applications. The project also includes the development of a simple mobile application by using MIT App Inventor. The objective of the mobile app is to create a mobile platform to control the USV and to show the previously gathered result of the sensor on the apps.